ENGINEERING STUDENTS’ PERCEPTION ABOUT LEARNING AND ITS VARIOUS TYPES OF ASSESSMENT (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2018)
Students’ perception of assessments can serve as a guiding light for improving overall educational practices. A questionnaire was collected from 80 engineering student to discover students' perceptions of different types of assessment and their overall perceptions of various type of assessments advantages in enhancing learning experiences. The majority of students strongly agreed that quiz and case study was beneficial and helpful for enhancing learning experience in engineering courses. On the contrary, project presentation, journal review, essay, interview, and demonstration was seemed unhelpful for students to enhance their learning experience. In terms of enjoyment, a discrepancy was found for what engineering students’ perceived as important assessment tools for learning and what they actually enjoy doing.
Keywords: critical thinking; learning experience; oral assessment; student perception; written-assessment